Synthesis of Furoxans from Styrenes under Basic or Neutral Conditions - Matsubara, Ryosuke; Saeki, Yuta; Li, Jianhua; Eda, Kazuo (Synthesis, 2013)
Furoxans (1,2,5-oxadiazole 2-oxides) can be synthesized from the corresponding styrenes using NOBF4 under basic or even almost neutral reaction conditions. Acid-sensitive functional groups are tolerated under the developed basic conditions. For the substrates having poor reactivity, almost neutral conditions (using pyridine equimolar to NOBF4) are suitable for better yields.
Keywords: heterocycles; nitrogen-containing compounds; furoxans; styrenes; cyclization